Middle Cerebral Artery Aneurysm "Neck Overhang": Decreased Postclipping Residual Using the Intersecting Clipping Technique. Issue 4 (26th February 2018) - Dimitriadis, Stavros; Qeadan, Fares; Taylor, Christopher L; Yonas, Howard; Carlson, Andrew P
Abstract: BACKGROUND: Middle cerebral artery (MCA) aneurysms continue to be viewed by many as primarily surgical entities. OBJECTIVE: To introduce a new, easily measurable dimension termed "neck overhang, " defined as the amount of the aneurysm that extends proximal to the 2 dimensionally defined "neck" and to evaluate the utility of the intersecting clipping technique (use of straight clip and intersecting fenestrated clip) to adapt to this overhanging segment's specific dimensions and achieve better obliteration of the MCA aneurysms. METHODS: We reviewed retrospectively 100 MCA aneurysms treated surgically over the last 10 yr at our institution. We identified the clipping technique that was performed (intersecting vs "standard" technique) and we evaluated the presence of a postoperative remnant. We then correlated these with the aneurysm's overhanging neck length. RESULTS: Forty-three aneurysms were treated with the intersecting clipping technique. The overall rate of remnant was 16%. In the standard group, the rate of remnant was 23%, whereas with intersecting clipping that was 7% ( P = .029). Within the standard clipping group, we found that the optimum threshold for length of the neck overhang was ≥1.9 mm in order to predict the occurrence of residual. Applying this threshold to the intersecting clipping technique group resulted in a reduction in remnant from 35% in the standard group to 9%. CONCLUSION: Neck overhang >1.9 mm is associated with a higher chance of postclipping residual aneurysm in MCA aneurysms. The intersecting clipping technique is a versatile technique that can conform to various aneurysms' geometry and can reduce the rate of post clipping residual for aneurysms with high neck overhang.